Bimbingan Berkelanjutan Mampu Meningkatkan Kompetensi Guru Menyusun RPP Berbasis Literasi Numerasi - Cicilia Sriningsih (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
The level of instruction provided in schools is significantly influenced by the students' literacy and numeracy skills. The literacy and numeracy skills of students are demonstrated through the education quality report cards. The outcomes of the students' numeracy literacy are still subpar at SD Negeri Gadingan, and a particular intervention with a value of 4% is required. This was due to the inability of three class teachers to effectively construct lesson plans based on numeracy and literacy. By Continuing Guidance activities at SD Negeri Gadingan, this School Action Research seeks to enhance teachers' capacity to create lesson plans that integrate numeracy and literacy. This type of study employed a qualitative methodology and was conducted from January to April 2022. Observation, documentation, and interviews were used in the data collection process. Teachers from SD Negeri Gadingan's grades IV, V, and VI served as the study's subjects. Data on the creation of lesson plans based on teachers' numeracy and literacy levels were collected. The three steps of data analysis were data reduction, data presentation, and conclusion-making. The study's findings demonstrated that continuing guidance could enhance teachers' competence. As the result, teachers' ability to create lesson plans improved by 93%, while students' literacy and numeracy learning skills improved by 89% with good criteria.